Digital Human Resource Management Practices in Enhancing Educational Staff Performance - Muhamad Ridwan; Sonya Sidjabat; Pipit Sundari; Nurhayati (Lembaga Publikasi Ilmiah Nusantara, 2026)
The increasing integration of digital technology in organizational management has encouraged educational institutions to adopt Digital Human Resource Management (DHRM) practices to improve workforce performance. However, prior studies have predominantly focused on the corporate sector, with limited attention to the implementation of DHRM in educational settings and its impact on educational staff performance. Moreover, the research gap lies in the lack of explicit examination of organizational and individual factors influencing DHRM effectiveness. This study aims to analyze the contribution of DHRM practices to enhancing educational staff performance and to identify key supporting factors. This research employed a qualitative case study approach at an educational institution, with participants selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that digital HR practices, including digital recruitment, online training, human resource information systems, and digital performance monitoring, improve administrative efficiency, strengthen competencies, and enhance transparency. The study also finds that staff digital literacy and accountability have increased. This study contributes by providing empirical evidence in the educational context and highlighting factors influencing DHRM success. It concludes that effective implementation requires organizational readiness, leadership support, and continuous professional development.